Strategi Pembangunan Kampung Iklim Kelurahan Eka Jaya dan Kelurahan Tanjung Sari Kota Jambi dengan Analisis SWOT - Umar, Putri Widya Saweri Gading; Marwoto, Marwoto; Sa’ad, Asmadi (Universitas Batanghari Jambi, 2025)
This study aims to formulate a development strategy for the Climate Village of Eka Jaya Village and Tanjung Sari Village in Jambi City using SWOT analysis. The instrument used to compile the company's strategic elements is the SWOT matrix. This matrix effectively describes how external opportunities and threats faced by the company can be aligned with its strengths and limitations. This matrix can provide four sets of potential strategy possibilities. The research findings indicate that the development approach for the Climate Village in Eka Jaya Village and Tanjung Sari Village shows significant potential. The main strengths of Eka Jaya are community dedication, local government involvement, and collaboration with the commercial sector. The main constraints are financial constraints and regulatory restrictions. The main opportunities are external funding and environmental laws, while the main risks are environmental degradation and climate change. In Tanjung Sari, the main strengths are ongoing commitment and stakeholder collaboration, while the main problems are financial constraints and political fluctuations. The main opportunities are external funding and program credibility, while the main risks are environmental degradation and climate change. The strategy includes enhancing strengths and opportunities while addressing weaknesses and threats.